2022
DOI: 10.1101/2022.06.15.496245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Mediator complex regulates enhancer-promoter interactions

Abstract: Enhancer-mediated gene activation generally requires physical proximity between enhancers and their target gene promoters. However, the molecular mechanisms by which interactions between enhancers and promoters are formed are not well understood. Here, we investigate the function of the Mediator complex in the regulation of enhancer-promoter interactions, by combining rapid protein depletion and high-resolution MNase-based chromosome conformation capture approaches. We show that depletion of Mediator leads to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 84 publications
5
15
0
Order By: Relevance
“…Normalizing to the local changes in background contacts highlight Pol II as a major factor that contributes to enhancer-promoter interaction frequency. Notably, our results are consistent with very new preprints that make use of the higher-resolution MNase-based 3C analyses following depletion of Pol II or Mediator ( 72, 73 ). Several aspects of Pol II may help facilitate interactions, especially under a hub model: First, the C-terminal heptad repeats on RPB1, the largest subunit of Pol II, have been shown to aid in macromolecular clustering ( 38, 41, 42, 65, 74, 75 ).…”
Section: Discussionsupporting
confidence: 87%
“…Normalizing to the local changes in background contacts highlight Pol II as a major factor that contributes to enhancer-promoter interaction frequency. Notably, our results are consistent with very new preprints that make use of the higher-resolution MNase-based 3C analyses following depletion of Pol II or Mediator ( 72, 73 ). Several aspects of Pol II may help facilitate interactions, especially under a hub model: First, the C-terminal heptad repeats on RPB1, the largest subunit of Pol II, have been shown to aid in macromolecular clustering ( 38, 41, 42, 65, 74, 75 ).…”
Section: Discussionsupporting
confidence: 87%
“…We combined experiments with in silico modeling to interpret the interplay between cohesin loop extrusion and RNAPII-mediated looping. In parallel to our study, an orthogonal one applying MCC to mouse cells acutely depleted of Mediator generated similar observations across different genomic loci (Preprint: Ramasamy et al, 2022).…”
Section: Introductionsupporting
confidence: 65%
“…Hi-C studies that followed this early work found Mediator and RNAPII to be dispensable for 3D chromatin folding (Jiang et al, 2020;El Khattabi et al, 2019). This is now challenged by MCC data showing loss of enhancer-promoter contacts following acute depletion of Mediator (Preprint: Ramasamy et al, 2022) and by decreased cohesin binding to RNAPII-transcribed genes following depletion of the yeast Med14 subunit (Mattingly et al, 2022). These new observations, together with the Micro-C analysis we present here, put the still-debated role of RNAPII in 3D chromatin folding in a different light.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we found that PLAC-seq shows a very weak enrichment of interactions at DHSs, even for those bound by CTCF. Thus, in line with other recent reports on MNase-based C-methods 6,30,31,3941 , our results suggest that MChIP-C achieves superior sensitivity and resolution compared to C-methods based on standard restriction enzymes.…”
Section: Resultssupporting
confidence: 92%